Kontestasi Metodologi Legislasi Usia Perkawinan di Indonesia - Khaidarulloh Khaidarulloh (Al-Syakhsiyyah: Journal of Law & Family Studies, 2022)
In many cases, the issue of marriage age is often a symbol of state intervention in modernizing the law. In addition to being a tool for carrying out social change, it also represents the occurrence of negotiations between religious and state paradigms, where in essence, both want the same benefits, namely certainty and guarantee of citizen’s rights. The research is based on literature data on how the discourse on the modernization of Islamic family law in the scope of the issue of marriage age has evolved in the literature. In addition, secondary data is also based on the latest developments in the rate of marriage dispensation cases in some religious courts spread across Indonesia. The results showed that, historically, marriage age was an important issue in the concept of modernization of Islamic family law; it became evidence of the existence of ideological contestation between religion and the state. However, the rampant cases of marriage dispensation in parts of Indonesia are also proof that the country's big project to change people's culture cannot be said to be successful, considering that the marriage age bill since 1973 has been rolled out. For this reason, synergy between state institutions to reduce the high number of marriage dispensations needs to be reviewed, thus finding weak points for the enactment of existing rules.